The IL-23/Th17 pathway inhibitors in the treatment of psoriasis and the risk of skin malignancies: a review - Krzysztofik, Marta; Brzewski, Paweł; Kulbat, Aleksandra; Masajada, Magdalena; Richter, Karolina; Wysocki, Wojciech M. (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2024)
Psoriasis and psoriatic arthritis are chronic inflammatory conditions that constitute a significant global health burden due to their prevalence and impact on quality of life. A deeper comprehension of psoriasis and psoriatic arthritis pathogenesis has recently led to the emergence of novel classes of biologics targeting the IL-23/Th17 pathway. The specific role of interleukin-12, -23, and -17 in cancer as either promoters or inhibitors is under investigation in various studies. Here, we explore the potential role of interleukin-12, -23, and -17 in the development of skin tumours as well as the safety of using their inhibitors in the treatment of psoriasis and psoriatic arthritis, particularly in relation to the risk of melanoma and non-melanoma skin cancer (NMSC) development.